Interacción de las redes sociales en tic sobre las competencias comunicativas y sociales para jóvenes escolarizados de sexto a undécimo grado (2021)
The purpose of this study is to describe the interaction of social networks in Tic on the communicative and social competences of young students from sixth to eleventh grade in Bucaramanga schools;